Pertanggunganjawaban Notaris Terhadap Pemindahan Hak Milik Atas Tanah Secara Kewarisan Kepada WNA - Iga Dewi, Elit; Alexsandro Ricardo, James; Prakoso, Bhim (LPPM Universitas Ekasakti Padang, 2024)
The Basic Agrarian Law regulates the prohibition on foreigners' ownership of private land. However, it cannot be denied that Indonesian residents can have foreign heirs. This research aims to determine and analyze the legal position of foreigners regarding ownership of land by inheritance using a notarial deed, as well as how the notary is accountable for the deeds they make. So this research is entitled Notary's Responsibility for the Transfer of Land Ownership Rights by Inheritance to Foreigners. This research was conducted using qualitative methods. The approach to this research uses a normative juridical approach. This research shows that the legal position of foreigners regarding ownership of land by inheritance is that a person's civil right to receive an inheritance can never be lost unless due to actions that endanger the heir who has died. For foreigners, they are not allowed to have ownership rights to land. Acquisition by means of sale and purchase, gift, exchange, gift by will, without stipulation by the government is considered null and void by law. Foreigners are required to relinquish the property rights they have acquired within 1 year of obtaining those rights. However, if the 1 year period has passed, the foreigner will lose ownership rights to the land and the ownership will change to state property.